VDC_100102370104.0X000001. Issue 2 (February 2018) - Maximus, Steven; Figueroa, Cesar; Whealon, Matthew; Pham, Jacqueline; Kuncir, Eric; Barrios, Cristobal
The focused assessment with sonography for trauma (FAST) examination has become the standard of care for rapid evaluation of trauma patients. Extended FAST (eFAST) is the use of ultra-sonography for the detection of pneumothorax (PTX). The exact sensitivity and specificity of eFAST detecting traumatic PTX during practical "real-life" application is yet to be investigated. This is a retrospective review of all trauma patients with a diagnosis of PTX, who were treated at a large level 1 urban trauma center from March 2013 through July 2014. Charts were reviewed for results of imaging, which included eFAST, chest X-ray, and CT scan. The requirement of tube thoracostomy and mechanism of injury were also analyzed. A total of 369 patients with a diagnosis of PTX were identified. A total of 69 patients were excluded, as eFASTwas either not performed or not documented, leaving 300 patients identified with PTX. A total of 113 patients had clinically significant PTX (37.6%), requiring immediate tube thoracostomy placement. eFAST yielded a positive diagnosis of PTX in 19 patients (16.8%), and all were clinically significant, requiring tube thoracostomy. Chest X-ray detected clinically significant PTX in 105 patients (92.9%). The literature on the utility of eFAST for PTX in trauma is variable. Our data show that although specific for clinically significant traumatic PTX, it has poor sensitivity when performed by clinicians with variable levels of ultrasound training. We conclude that CT is still the gold standard in detecting PTX, and clinicians performing eFAST should have adequate training.